2008
DOI: 10.1111/j.1747-0765.2007.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of acid phosphatase activities in the roots of white lupin plants grown under phosphorus-deficient conditions

Abstract: Acid phosphatase (APase) produced by the cluster roots of white lupin (Lupinus albus L.) plays an important role in inorganic phosphate (Pi) acquisition. Although the importance of cluster roots in Pi acquisition is well known, information on the distribution of APase within tissues of normal and cluster roots is lacking. Isoelectric focusing of APase isoforms as well as histochemical localization and visualization of APase were used to clarify the importance of secretory APase for P nutrition of white lupin g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Our other studies showed the strong activity of APases detected in the root epidermis (and outer cortex cells) of different oat varieties, which indicated that at least a part of these enzymes might be secreted from the roots to the ground (data not published). Histochemical visualization of APases activity in roots of white lupine also showed a strong enzyme activity in the epidermis and root hairs under Pi deficiency (Wasaki et al 2008); white lupine can produce both cell wall-bound APase and enzymes than can be released into the rhizosphere, LASAP2, a form of secreted APase from white lupin roots (Wasaki et al 2008). Similarly, in Arabidopsis under Pi starvation a strong expression of the promoter region of secreted APases was detected in young lateral roots and in the vascular tissues (Haran et al 2000).…”
Section: Cultivarmentioning
confidence: 99%
See 1 more Smart Citation
“…Our other studies showed the strong activity of APases detected in the root epidermis (and outer cortex cells) of different oat varieties, which indicated that at least a part of these enzymes might be secreted from the roots to the ground (data not published). Histochemical visualization of APases activity in roots of white lupine also showed a strong enzyme activity in the epidermis and root hairs under Pi deficiency (Wasaki et al 2008); white lupine can produce both cell wall-bound APase and enzymes than can be released into the rhizosphere, LASAP2, a form of secreted APase from white lupin roots (Wasaki et al 2008). Similarly, in Arabidopsis under Pi starvation a strong expression of the promoter region of secreted APases was detected in young lateral roots and in the vascular tissues (Haran et al 2000).…”
Section: Cultivarmentioning
confidence: 99%
“…APases expression is mediated by different environmental and developmental factors, including Pi deficit (Duff et al 1994;Olczak et al 2003). Under low Pi conditions the activities of extracellular and/or internal APases are often increasing; additionally, some plants might secrete nonspecific APase from roots to the rhizosphere (Duff et al 1994;Gilbert et al 1999;Yun and Kaeppler 2001;Wasaki et al 2008). Specific acid phosphatases that exhibit phytasic activities (phosphohydrolases with the capability of initiating dephosphorylation of myoinositol-hexakisphosphate) are active not only mainly in germinating seeds but also in cells of primary roots (Asmar 1997;Richardson et al 2000;Gregory 2006).…”
Section: Ciereszko (And) á E _mentioning
confidence: 99%
“…White lupin secretes copious amounts of APases from its roots and proteoid roots when subjected to Pi starvation (Miller et al, 2001, Wasaki et al, 2008.…”
Section: Nutrition Parameter Phosphate Treatmentmentioning
confidence: 99%
“…Histochemical visualization of APases activity for cluster roots of white lupine, developed under Pi deficiency, indicated high enzyme activity in the epidermis and root hairs (Wasaki et al 2008). LASAP2 is believed to be a major form of secreted APase, released from white lupine roots into the rhizosphere (Wasaki et al 2009).…”
Section: Distribution Of Apase Activity In Root Tissuesmentioning
confidence: 99%
“…Various developmental and environmental conditions may influence gene expression, protein synthesis, and activity of APases in plant tissue or in soil (Duff et al 1994;_ Zebrowska and Ciereszko 2009). Activities of both extracellular and internal APases might increase in response to phosphorus depletion and several plants can secrete APase from roots to the rhizosphere (Duff et al 1994;Gilbert et al 1999;Wasaki et al 2008;Tran et al 2010). Extracellular APases are involved in Pi release from organic phosphate monoesters in soils, whereas intracellular APases are thought to be pivotal in the remobilization of Pi from phosphorus-rich components in cells (Duff et al 1994;Tomscha et al 2004;Tran et al 2010).…”
Section: Introductionmentioning
confidence: 99%